The effect of Infrastructure on Private Investment: a case study in Developing Countries - Juliani Pudjowati; Olyvia Rosalia; Firayani (PT. Anagata Sembagi Education, 2025)
This study investigates the impact of infrastructure development on private investment in developing countries using panel data regression analysis. Infrastructure is widely acknowledged as a key driver of economic growth and investment attractiveness. By analyzing data from multiple developing nations over a ten-year period, the research explores the significance and direction of the relationship between infrastructure quality and the level of private investment. The findings indicate that infrastructure has a positive and statistically significant effect on private investment, with key elements such as road networks, electricity supply, and internet connectivity showing the strongest influence. The model also includes control variables such as GDP per capita, inflation, political stability, and tax burden, which further highlight the complex dynamics influencing investment flows. The study reveals that institutional readiness and government policies play an important moderating role. In countries with poor infrastructure and weak governance, the positive effects are less pronounced. These results underscore the importance of balanced infrastructure development and strong regulatory frameworks to support sustainable private investment growth in developing economies. The study offers key policy implications and highlights the need for future research that incorporates institutional quality and investor perception variables.